The Impact of Leadership and Work Discipline on Employee Performance at Empat Putra Utama Bersama Ltd - Pascha, Dwiky; Kustini, Kustini (International Journal of Asian Business and Management, 2023)
The goal of this research was to identify the influence between leadership and work discipline towards the Empat Putra Utama Bersama Ltd employees’ performance. This research focused on the quantitative method. Furthermore, the researcher varied the population from supervisors and field staff of Empat Putra Utama Bersama Ltd which consisted of 46 respondents. Saturated sampling were employed in this reserch’s sampling procedure. The data analysis technique utilized PLS (Partial Least Square) method. The research has discovered that work discipline and leadership correlated and affected to the Empat Putra Utama Bersama employees’ performance